Paraoxonase-2 variants potentially influence insulin resistance, beta-cell function, and their interrelationships with alanine aminotransferase in type 2 diabetes - Qujeq, Durdi (J Res Med Sci, 2018)
BACKGROUND: The aim of this study was to determine whether insulin resistance, beta-cell function, and their associations with alanine aminotransferase (ALT) are affected by the functional variants of paraoxonase-2 (PON2) as an intracellular antioxidant in patients with type 2 diabetes (T2D). MATERIALS AND METHODS: Quantitative insulin sensitivity check index (QUICKI) and homeostasis model assessment for beta-cell function (HOMA-BCF) were assessed in T2D patients. Insulin levels were determined using ELISA. The variants PON2-A148G and PON2-S311C were genotyped using polymerase chain reaction-based restriction fragment length polymorphism. RESULTS: According to the PON2-G148A variant, ALT was found to be significantly correlated with QUICKI (r = −0.616, P = 0.005) and HOMA-BCF (r = 0.573, P = 0.01) in the GA + GG group; however, the correlations were not statistically significant in the AA genotypes. Based on the genotypes of PON2-S311C, there was a significant correlation between ALT with QUICKI (r = −0.540, P = 0.031) and HOMA-BCF (r = 0.567, P = 0.022) in the SC + CC group. In the multiple adjusted logistic regression analyses, considering the variants PON2-G148A and PON2-C311S as independent variables and QUICKI and HOMA-BCF as the dependent variables, both variants were significantly associated with the QUICKI (P = 0.019 for PON2-G148A and P = 0.041 for PON2-C311S). Furthermore, PON2-C311S remained significantly associated with HOMA-BCF (P = 0.03). CONCLUSION: These data implicate a role for the functional variants of PON2 in insulin resistance and beta-cell function as well as underscore the effective role of these variants in the associations between them and ALT. Our data contribute to our understanding of the important physiologic functions of PON2 in glucose metabolism and its related metabolic diseases.